Toward a Theory of Tuition: Prices, Peer Wages, and Competition in Higher Education - Gordon C. Winston (Williams College, Williams Project on the Economics of Higher Education (WPEHE), 2003)
College tuition, as the price of higher education services, defies familiar economic analysis in important ways. It is recognized that tuition is a price that covers only a fraction of the cost of producing those educational services (about a third, nationally), creating an in-kind subsidy for students (the balance being made up by large flows of donative resources from gifts, appropriations, and returns on wealth). This paper examines yet another important economic peculiarity of tuition; it takes seriously input and output markets implied by Rothschild-White (1995 JPE) in which a single event - of a student?s matriculation - is simultaneously a transaction in both an input market (where a wage is paid for a student?s peer quality) and an output market (where a price is paid for the college?s educational services). Those two prices are obscured by the fact that the peer wage is paid in the form of a discount on the price of educational services as well as by the fact that the schools? sales (tuition) revenues are significantly augmented by those donated resources. This framing sees a school?s access to donated resources (wealth) critical in determining which market - peer quality inputs or educational services sales - will most influence its behavior. Apparent anomalies in the product market - like queues of unsatisfied customers that persist while schools refuse to expand capacity - disappear when they are seen to be the result of an input market where a queue of job applicants is used to allow the firm to select on worker - peer - quality (the result of an Akerlof- Yellen efficiency wage).
Keywords: 330; Studienfinanzierung; Wettbewerb; Lohn; Marktmechanismus; Bildungsökonomik; Theorie